2019
DOI: 10.1038/s41598-019-39418-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapalog resistance is associated with mesenchymal-type changes in Tsc2-null cells

Abstract: Tuberous Sclerosis Complex (TSC) and Lymphangioleiomyomatosis (LAM) are caused by inactivating mutations in TSC1 or TSC2 , leading to mTORC1 hyperactivation. The mTORC1 inhibitors rapamycin and analogs (rapalogs) are approved for treating of TSC and LAM. Due to their cytostatic and not cytocidal action, discontinuation of treatment leads to tumor regrowth and decline in pulmonary function. Therefore, life-long rapalog treatment is proposed for the control of TSC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 71 publications
2
19
0
Order By: Relevance
“…In this study, we observed that xenograft tumors of ELT3 cells potently responded to rapamycin within 1 week of treatment, however, tumors became refractory from week 2 of rapamycin treatment. This rapamycin resistant growth is consistent with the study by Valianou et al [61]. In our xenograft tumor study, we used bioluminescent imaging approach to quantify the tumor growth in response to rapamycin treatment, enabling quantification of viable tumor cells in vivo.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, we observed that xenograft tumors of ELT3 cells potently responded to rapamycin within 1 week of treatment, however, tumors became refractory from week 2 of rapamycin treatment. This rapamycin resistant growth is consistent with the study by Valianou et al [61]. In our xenograft tumor study, we used bioluminescent imaging approach to quantify the tumor growth in response to rapamycin treatment, enabling quantification of viable tumor cells in vivo.…”
Section: Discussionsupporting
confidence: 87%
“…A potential mechanism by which active-site mTOR or dual inhibitors of PI3K/mTOR promotes MEK1/2-MAPK signaling pathway activation is via enhanced EGFR activity. A recent RNAseq analysis by Valianou et al identified rapamycin-induced upregulation of EGFR signaling pathway in rapamycin-resistant ELT3 cells [61]. The EGFR tyrosine kinase activity and affinity for its ligands are negatively regulated by protein kinase C (PKCα) via phosphorylation at Thr654 [70].…”
Section: Discussionmentioning
confidence: 99%
“…We may speculate that oncogenic EVI1 in ccRCC is linked to the acquisition of stem cell-like and/or EMT features, as described in other cancer types [5][6][7][8][9][10]. It is of particular note that EMT has also been associated with resistance to allosteric mTOR inhibition [37,38]. The precise causal variants linked to the observed genetic associations are also unknown.…”
Section: Discussionmentioning
confidence: 94%
“…(9) NR2F2: activated RAS upregulates COUP-TFII and increases lactate production; overproduction of lactate disrupts the interaction of TSC2 and Rheb to increase mTORC1 activity. use, but it comes with a risk of remarkable adverse effects and possible acquired rapalog resistance (16). Moreover, LAM patients with lymphatic involvement may respond to sirolimus with a greater improvement in lung function than those without lymphatic disease, indicating that not all patients respond to rapamycin therapy in the same way (25,26).…”
Section: Rapamycin Is An Inhibitor Of Mtorc1 But Not a Perfect Cure Fmentioning
confidence: 99%